2000
DOI: 10.1016/s1010-7940(00)00537-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting long-term survival after en-bloc resection of lung cancer invading the chest wall✩

Abstract: Objective: Several reports emphasize the importance of en-bloc resection as the optimal surgical treatment of lung cancer with chest wall invasion. We investigated possible factors which could affect long-term survival following radical resection of these tumors. Methods: Between 1981 and 1998, 100 patients (90 male; ten female), with a median age of 60 years (36±84), underwent radical en-bloc resection of non-small cell lung cancer (NSCLC) with chest wall involvement. Patients with superior sulcus tumors inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 19 publications
6
33
0
3
Order By: Relevance
“…Lymphnodal infiltration and completeness of resection appear to be the main survival predictors in the univariate analysis: nodal status and not the completeness of resection (probably for the small number of R1 patients) maintained its significance in the multivariate analysis. These results have been observed also in the previous literature and are universally accepted [2,3,7]. However, the impact of these two factors on long-term survival is so important that secondary factors like extension of infiltration, surgical strategy and postoperative treatment were often difficult to define especially in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Lymphnodal infiltration and completeness of resection appear to be the main survival predictors in the univariate analysis: nodal status and not the completeness of resection (probably for the small number of R1 patients) maintained its significance in the multivariate analysis. These results have been observed also in the previous literature and are universally accepted [2,3,7]. However, the impact of these two factors on long-term survival is so important that secondary factors like extension of infiltration, surgical strategy and postoperative treatment were often difficult to define especially in a multivariate analysis.…”
Section: Discussionsupporting
confidence: 77%
“…However, the impact of these two factors on long-term survival is so important that secondary factors like extension of infiltration, surgical strategy and postoperative treatment were often difficult to define especially in a multivariate analysis. In his series of 104 surgically resected patients, Chapelier found that patients with a tumour infiltration confined to the parietal pleura had a significantly better 5-year survival than those with chest wall infiltration [3]. Deeper involvement was advocated as a predictor of worse prognosis also by Mischina et al [9] and in a recent report by Facciolo et al [4], who found that depth of tumour invasion affected prognosis in the sub-group of pN0 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest wall resection is routinely perfomed ''en-bloc'' with the lung specimen, with perioperative mortality rates of 1-4% [111][112][113]. 5-year survival rates of 40-50% have been reported in patients with stage T3N0M0 disease, but of ,20% in patients with stage IIIa disease [111][112][113].…”
Section: Chest Wall Resectionmentioning
confidence: 99%
“…Chest wall defects can be reconstructed or not depending upon their size and location. Various materials are routinely used to repair the chest wall: methyl metacrylate, polytetrafluoroethylene (PTFE), metallic rods and plates with excellent long-term results [110][111][112][113]. In patients whose tumour infiltrates into the parietal pleura only, en-bloc chest wall resections provide a much better survival than extrapleural resections [111].…”
Section: Chest Wall Resectionmentioning
confidence: 99%